VALIDASI METODE ANALISIS SPEKTROFLUOROMETRI UNTUK PENETAPAN KADAR SIPROFLOKSASIN GENERIK DALAM SAMPEL URINMANUSIA - Dwi Cahyani, Erlien (Widya Warta, 2020)
Ciprofloxacin tablet generic usage has been increasing recently due to its economically reason. The generic tablet needed to assure its bioequivalence towards the innovator, one of them by determining  total  amount  of  ciprofloxacin  excreted  in  urine.  The  aim  of  this  research  was  to validate  the  simple,  selective  and  sensitive  spectrofluorometric  analysis  method  to  determine total  amount  of  ciprofloxacin  excreted  in  human  urine  sample  that can  be  developed  for bioequivalence  study  purpose.    Urine  samples  were  obtained  from  the  subjects  of  six  healthy men  who  were  asked  to  take  ciprofloxacin  tablet.  The  assay  of  ciprofloxacin  in  tablet preparation  were  tested  its  validation  according  to  linearity,  accuracy,  precision,  limits  of detection  (LOD)  and  limits  of  quantitative  (LOQ).  The  validation  parameter  with  analysis method  obtained  linear  regression  curve  Y  =  0,6878X  +  2,8332  (r  =  0,9994)  with  limits  of detection  and  limits  of  quantitation  were0,0721  μg/ml  and  0,2402  μg/ml  respectively, coefficient  of  variation  of  0,0036%,  and  accuracy  value  of  92,81  %.  The  total  amount  of ciprofloxacin excreted was within the range of 270,19 μg/ml to 341,91 μg/ml.